Healing dramas: divination and magic in modern Puerto Pico - Romberg, Raquel (University of Texas Press, 2009)
Introduction : healing dramas -- A flight perfected at death : mimetic memories of a brujo -- Dreams -- Drama -- Spiritual time -- The sentient body -- Space -- Epilogue : a farewell trabajo